Effect of Ganglioside GM3 Synthase Gene Knockout on the Glycoprotein N‐Glycan Profile of Mouse Embryonic Fibroblast. Issue 1 (7th December 2012) - Nagahori, Noriko; Yamashita, Tadashi; Amano, Maho; Nishimura, Shin‐Ichiro
Abstract The structural and clinical significance of cellular glycoproteins and glycosphingolipids (GSLs) are often separately discussed. Considering the biosynthetic pathway of glycoconjugates, glycans of cell‐surface glycoproteins and GSLs might partially share functions in maintaining cellular homeostatis. The purpose of this study is to establish a general and comprehensive glycomics protocol for cellular GSLs and N‐glycans of glycoproteins. To test the feasibility of a glycoblotting‐based protocol, whole glycans released both from GSLs and glycoproteins were profiled concurrently by using GM3 synthase‐deficient mouse embryonic fibroblast GM3(−/−). GM3(−/−) cells did not synthesize GM3 or any downstream product of GM3 synthase. Instead, expression levels of o‐series gangliosides involving GM1‐b and GD1‐α increased dramatically, whereas a‐/b‐series gangliosides were predominantly detected in wild‐type (WT) cells. We also discovered that glycoprotein N‐glycan profiles of GM3(−/−) cells are significantly altered as compared to WT cells, although GM3 synthase is responsible only for GSLs synthesis and is not associated with glycoprotein N‐glycan biosynthesis. The present approach allows for high‐throughput profiling of cellular glycomes enriched by different classes of glycoconjugates, and our results demonstrated that gene knockout of the enzymes responsible for GSL biosynthesis significantly influences the N‐glycans of glycoproteins.